Factors affecting the grain pollen germination of yellow passion fruit: culture medium and agrotoxics - da Silva, Mairon Moura; Bruckner, Claudio Horst; Picanço, Marcelo; Cruz, Cosme Damião (Pesquisa Agropecuaria Brasileira, 1999)
Temperature, culture medium, incubation period and pH for yellow passion fruit (Passiflora edulis f. flavicarpa) pollen germination, as well the effect of agrotoxics were studied. Temperature of 28 ± 0.5°C, culture medium with 50 g/L of sacarose, 0.2 g/L of boric acid and 1.0 g/L of calcium nitrate showed better germination of P. edulis f. flavicarpa pollen. No effect of the incubation period (17 and 48 hours) was registered for pollen germination of this plant. Percentage of pollen germination of P. edulis f. flavicarpa was not affected by the acaricid Dicofol + Tetradifon and by the insecticides Cartap, Fenpropathrin, and Abamectin. There was a small reduction in pollen germination in the presence of insecticides Malathion, Fenthion, Thrichorfon, Vamidothion, Deltamethrin, Methyl Parathion and the spreader-sticker N-dodecil benzen sodium sulphate. Ethion and Lambdacyhalothrin had severe effect on pollen germination of this plant.